The Feasibility of ’BEYB’ Attacking Tactic Training in Futsal Game - Badru, Benny (Jurnal Pendidikan Indonesia, 2021)
The game of futsal is a game that prioritizes speed so that the futsal is known as a sport that has high intensity. This study aims to develop a training model of BEYB attack tactics in futsal games. The research method uses the development method from Borg and Gall. The research was conducted at the Futsal Sports Hall, State University of Makassar. The subjects in this study were Futsal Athletes. Based on the data obtained, from the results of field trials and discussion of research results, it can be concluded that: through the validity test carried out using the expert justification test, the product is a training model to attack BEYB in futsal games as many as 40 training models. The attack tactics training model with patterns such as 2-2, 1-2-1, 3-1, and power play has been developed to be more varied and can be used in the attacking systems and formations that will be used. BEYB attacking training model can be applied in this futsal game, extracurricular teachers, especially futsal, should be reviewed so that athletes can do it according to their abilities and motor development.